Volume 1B: Marine; Microturbines, Turbochargers and Small Turbomachines; Steam Turbines 2014
DOI: 10.1115/gt2014-25456
|View full text |Cite
|
Sign up to set email alerts
|

On the Prediction and Theory of the Temperature Increase of Low Pressure Last Stage Moving Blades During Low Volume Flow Conditions, and Limiting it Through Steam Extraction Methods

Abstract: During extreme low volume flow conditions, the last stages of a low pressure steam turbine operate in ventilation conditions that can cause a significant temperature increase of critical regions of the last stage moving blade. Under some conditions, the blade temperature may rise above a safe operating temperature, requiring the machine to be shut down. Limiting the heating effect on the last stage moving blade increases the allowable operating range of the low pressure turbine. One common method is to spray w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Further research by Sigg and Rice 12 showed that the system RI was influenced by the exhaust shape. Nonsynchronous unsteady aerodynamic excitations in the last stage were also found by Liu et al 13 and Tanuma et al 14 Besides the flow fluctuation, Beevers et al 15 and Mambro et al 16,17 found that in this region, due to lack of axial flow, heat was difficult to dissipate through convection, and the temperature of the flow increased abnormally, which caused the LSMB tip and the casing to be in high temperature.…”
Section: Introductionmentioning
confidence: 60%
“…Further research by Sigg and Rice 12 showed that the system RI was influenced by the exhaust shape. Nonsynchronous unsteady aerodynamic excitations in the last stage were also found by Liu et al 13 and Tanuma et al 14 Besides the flow fluctuation, Beevers et al 15 and Mambro et al 16,17 found that in this region, due to lack of axial flow, heat was difficult to dissipate through convection, and the temperature of the flow increased abnormally, which caused the LSMB tip and the casing to be in high temperature.…”
Section: Introductionmentioning
confidence: 60%
“…Baseload thermal power plants must operate under variable loads due to wind and solar energy share. Steam turbines are subject to severe operating conditions [5,6], and rotor last stage blades can operate in a compressor mode delivering energy to the working fluid in low volume flow conditions [7]. Concepts of a dynamic power plant and solutions for an operational flexibility enhancement appear more often in the literature [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%